Dry matter yield and phosphorus concentration of an association Brachiaria humidicola-Stylosanthes guianensis - Domínguez Pérez, Félix Daniel; Bolaños Aguilar, Eduardo Daniel; Lagunes Espinoza, Luz del Carmen; Salgado García, Sergio; Ramos Juárez, Jesús; Guerrero Rodríguez, Juan (Revista Mexicana de Ciencias Agrícolas, 2017)
The study was conducted in a meadow of Huimanguillo, Tabasco, established in a soil with acidic pH and low contents of N, P and K, from October 2014 to July 2015, including the northeastern, dry and rainy seasons. The objective was to evaluate the effect of phosphate fertilization on the yield of dry matter (RMS), seasonal distribution of forage and phosphorus concentration (P) of an associated meadow B. humidicola-S. guianensis and one in monoculture of B. humidicola. The plots of B. humidicola in monoculture without and with phosphate fertilization (H, HF) and of the association without and with phosphate fertilization (HS, HSF), established in a completely randomized design with four replications, were analyzed in repeated measurements. The RMS and P were measured every 35 days from October 7, 2014 to July 14, 2015. The total RMS was similar between H, HF and HSF (10.5 vs 7.07 t ha-1 in HS), although the RMS of the associated grasslands (HS, HSF) showed less variation in time. The associated grasslands showed higher RMS in the dry season, and the prairies in monoculture in rains. The concentration of phosphorus in the biomass of S. guianensis and in the one of the fertilized treatments (HF, HSF) was higher than in the one of the treatments without fertilizing (H, HS). The number of nodules per plant was increased by phosphate fertilization (18.8 in HSF vs 13.9 HS, average of the three seasons), but not the RMS in roots
Keywords: forage yield; grass-legume associated pasture; seasonal distribution of dry matter; tropical forage legumes